American Frontier : Forever Texas - Book 1 - Johnstone, William W.; Johnstone, J. A. (New York : Kensington Publishing Corp., 2022)
Its 1852. The wounds of the Mexican War are healing. Regis Royle, co-owner of a steamship fleet, has made it out alive, relatively unscarred and with enough profit and foolhardy ambition to envision a new life in south Texas. With the help of his crack-shot kid brother Shepley, his glad-handing riverboat partner Cormac Delany, and his old friend, raw-edged former Texas Ranger Jarvis "Bone" McGraw, Regis is laying claim to the prime jewel in a magnificent rolling prairie: the Santa Calina range teeming with wild mustangs, cattle, and eighteen-thousand acres of lush promise. But all dreams have a price. For Regis, its hell to pay--and the fire is coming at him from all directions. The brothers Royle and their partners have the most to lose--including their lives. They made a pledge to themselves to build the greatest ranch in America. To see it through to the end, theyll have to ride hard and learn the bitter necessity of violence and bloodshed.
Keywords: Brothers -- Fiction; Frontier and pioneer life -- Fiction; Ranchers -- Fiction; Cowboys -- Fiction; Texas -- Fiction; West (U.S.) -- History -- 1860-1890; Fiction; Western fiction